Detection of an Optical Signal Using Difference Frequency Generation in a Periodically Poled LiTaO3 Microwave Waveguide. (23rd November 2008) - Murata, Hiroshi; Okamura, Yasuyuki
Abstract : The detection of an optical signal modulated at 15 GHz was demonstrated experimentally by using difference frequency generation based on a second-order nonlinear optical effect in a periodically poledLiTaO 3 microwave rectangular waveguide. The measured frequency dependence of the generated microwave signal was in good agreement with the theoretically expected result. An interesting application of the proposed device is the detection of high-speed optical clock detection.